2021
DOI: 10.1124/jpet.121.000584
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Integrated Pharmacokinetic-Pharmacodynamic Model to Evaluate Combination Therapy and Determine In Vivo Synergism

Abstract: Understanding pharmacokinetic (PK)-pharmacodynamic (PD) relationships is essential in translational research. Existing PK-PD models for combination therapy lack consideration of quantitative contributions from individual drugs, whereas interaction factor is always assigned arbitrarily to one drug and overstretched for the determination of in vivo pharmacologic synergism. Herein, we report a novel generic PK-PD model for combination therapy by considering apparent contributions from indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Zhou et al reported that codelivering doxorubicin and a transforming growth factor beta (TGF-β) receptor inhibitor via a nanocarrier effectively inhibits the TGF-β/Smad signaling pathway, resulting in suppressed EMT progression in breast cancer cells . Notably, the distinct pharmacokinetic profiles of different drug components can introduce complexities that may affect the synergistic effects of combined therapy in vivo . In our study, NPs were developed by combining ACS (ARG-conjugated CS) and TFD (TPGS-conjugated FD), and incorporating the amino acid ARG into ACS endowed the NPs with a net positive charge at pH 7.0 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhou et al reported that codelivering doxorubicin and a transforming growth factor beta (TGF-β) receptor inhibitor via a nanocarrier effectively inhibits the TGF-β/Smad signaling pathway, resulting in suppressed EMT progression in breast cancer cells . Notably, the distinct pharmacokinetic profiles of different drug components can introduce complexities that may affect the synergistic effects of combined therapy in vivo . In our study, NPs were developed by combining ACS (ARG-conjugated CS) and TFD (TPGS-conjugated FD), and incorporating the amino acid ARG into ACS endowed the NPs with a net positive charge at pH 7.0 .…”
Section: Discussionmentioning
confidence: 99%
“… 58 Notably, the distinct pharmacokinetic profiles of different drug components can introduce complexities that may affect the synergistic effects of combined therapy in vivo . 59 In our study, NPs were developed by combining ACS (ARG-conjugated CS) and TFD (TPGS-conjugated FD), and incorporating the amino acid ARG into ACS endowed the NPs with a net positive charge at pH 7.0. 60 After acid hydrolysis of the ester bond in TPGS and TFD, the resulting solutions were analyzed by using LC–MS.…”
Section: Discussionmentioning
confidence: 99%
“…From this perspective, H9 is expected to accelerate HER2-mediated PI3K/AKT inhibition and ameliorate TIC through AMPK activation. Already, these dual-targeting mechanisms of H9 combined with trastuzumab exerted stronger anti-cancer activity by inhibiting PI3K/AKT and activating AMPK than did either drug individually, producing a synergistic effect by inducing apoptosis in mice bearing a breast tumor with combination index (CI) values less than 1 (CI = 0.647) [20,32,37,38].…”
Section: Introductionmentioning
confidence: 99%
“…The pharmacological effect of a certain drug is dependent on both its pharmacok netic (PK) and pharmacodynamic (PD) properties. The effects of PPB on the PK of antib otics have been studied extensively [10], but whether PPB also affects PD and antimicr bial activity (by reducing the non-protein-bound fraction) continues to be debated [11 This may be due to a lack of standardized in vitro PD models to quantify the impact PPB of antimicrobials [12]. These divergent results may be due to the use of different e perimental media with different protein amounts and types [13,14] or the heterogeneou methods (time-kill curves, MIC assays, dynamic models) used to study the effects of PP in vitro.…”
Section: Introductionmentioning
confidence: 99%